Differences In Lipid Profiles Based on Physical Activity Levels Among First-Year Students In a Medical Education Research Program - Ida Ayu Eka Widiastuti; Seto Priyambodo; Rifana Cholidah (Postgraduate, University of Mataram, 2023)
Regular physical activity with adequate intensity, according to WHO recommendations, can prevent various chronic diseases, such as heart disease, diabetes mellitus, cancer, and bone disease. Physical activity can improve lipid profil: triglycerides, total cholesterol, HDL cholesterol (HDL-C), and LDL cholesterol (LDL-C). The aim of this study was to compare lipid profiles, which include levels of triglycerides, total cholesterol, HDL cholesterol (HDL-C), and LDL cholesterol (LDL-C) at different levels of physical activity: low, medium, and high levels of physical activity. This study was an observational analytic study using a cross-sectional study. The subjects of this study were 93 first year students of the Medical Study Program, Faculty of Medicine, University of Mataram. The level of physical activity was assessed using the International Physical Activity Questionnaire-Short Form (IPAQ-SF) questionnaire and the lipid profile levels were measured using the enzymatic calorimetric method. The Kruskal-Wallis test was performed to assess the comparison of triglyceride levels between groups with low, medium and high activity levels, One-way ANOVA test for total cholesterol, LDL-C and HDL-C levels, and Post Hoc LSD for HDL-C. Of the 93 subjects, 36 (38.71%) had low levels of physical activity, 49 (52.69%) moderate physical activity, and only 8 (8.6%) had high levels of physical activity. There was a significant difference in HDL-C in the high-moderate physical activity level (p=0.006), high-low physical activity level (p=0.006), and medium-low physical activity level (p=0.022). Based on the results of this study, it can be concluded that there are significant differences in HDL-C at all levels of physical activity. Regular, measured physical activity of moderate to high intensity can increase HDL-C